Tipuri de interpolări în traducerile românești laice din secolul al XVIII-lea - Eugenia Dima (Revista de Istorie și Teorie Literară)
Following the structural changes in the Romanian society and of the influence of Enlightenment, at the beginning of the 18th century there was a gradual passage from the prevalent religious literature towards lay texts and lay translations. As a result of the modification of acculturation, the importance of lay translations from Western writings increased considerably. The paper draws attention upon the differences between the religious translations, in which faithfulness to the original generated little intervention into the sacred text (mainly of a linguistic character, of the explanatory interpolation type), and the interventions of lay text translators upon the originals, especially in the scientific areas, interventions called by the author (con)textual interpolations. The author proposes a possible taxonomy of these interpolations and tries to account for their motivations: the correction of some mistakes, the completion of missing details, the adequacy to the realities of the age, the connection to the Enlightenment ideology, the expression of opinions or feelings of the translator, etc. The classification is sustained by examples from translations in the 18th century.